2008
DOI: 10.1063/1.2955707
|View full text |Cite
|
Sign up to set email alerts
|

Role of C in the formation and kinetics of nanovoids induced by He+ implantation in Si

Abstract: The formation and growth of nanovoids in a C-doped Si layer after He+ implantation and thermal annealing are reported. A structure consisting of 240 nm of Si, 20 nm of Si doped with C at 0.8 at. %, and 240 nm of Si cap was realized by molecular beam epitaxy onto a 100 Si Czochralsky substrate. Three sets of samples were implanted with He+ at 30 keV and different doses of 81015, 31016, and 51016 cm−2 and subsequently annealed at 800 °C in N2 atmosphere. Cross-section transmission electron microscopy was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…8-15. In those studies, the epitaxial SiGe layer of under-critical thickness was first grown in a compressively strained state. Ion implantation of heavy (Ge, As, or Sn) [8][9][10][11] or light (He, H) [12][13][14][15] ions was used for the generation of point defects. It was demonstrated that the strained SiGe layers accumulate the implantation-induced vacancies followed by their thermally assisted evolution into voids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8-15. In those studies, the epitaxial SiGe layer of under-critical thickness was first grown in a compressively strained state. Ion implantation of heavy (Ge, As, or Sn) [8][9][10][11] or light (He, H) [12][13][14][15] ions was used for the generation of point defects. It was demonstrated that the strained SiGe layers accumulate the implantation-induced vacancies followed by their thermally assisted evolution into voids.…”
mentioning
confidence: 99%
“…It was demonstrated that the strained SiGe layers accumulate the implantation-induced vacancies followed by their thermally assisted evolution into voids. [8][9][10][11][12][13][14][15] The voids were of nanometer size and strictly assembled within the strained SiGe layers buried in the Si matrix. [8][9][10][11] More recently, the ability to collect vacancies and low-size gas atoms in compressively strained SiGe layers was used for the enhancement of exfoliation in advanced Smart-Cut technology by using either hydrogen ion implantation 14 or plasma treatment.…”
mentioning
confidence: 99%
“…The authors interpret the enhancement of cavity nucleation in relatively thick layers ͑20 nm͒ as a consequence of the strain induced by the C incorporation in the Si lattice. 12 However, applications require a detailed experimental and theoretical analysis of the effect of enhanced cavity nucleation along embedded SiGe ͑Ge͒ or Si:C layers on the relaxation process of SiGe layers, not available up to date. Here, we report on the use of a buried ultrathin Si:C layer ͑␦-Si: C͒ on the Si͑100͒ substrate to improve the relaxation of epitaxial strained Si x Ge 1−x structures.…”
mentioning
confidence: 99%
“…The preferential nucleation of He platelets in the Si substrate can be realized by the introduction (epitaxial growth) of an "impurity" layer which either reduces the energy associated with cavity formation, e.g., a SiGe layer 24,25 or by creating additional volume for He accumulation through introduction of smaller substitutional atoms, e.g., Si:C layer. 26,27 Such structures localize and homogenize the planar distribution of the dislocation loop sources (platelets) sensibly increasing the SiGe degree of relaxation. 27 …”
mentioning
confidence: 99%